Experimental investigation of cyclic durability and impact resistance of bellows of leveling device / N.Y. Khlopenko, S.A. Gavrilov // Problems of Tribology. – 2012. – № 1. – Р. 80-82. - Хлопенко, Н.Я.; Гаврилов, С.А. (Problems of Tribology, 2014)
The accordance of calculations and tests of cyclic durability and impact resistance of bellows of hydraulic leveling device has been defined [patent №46214 (Ukraine)].